Waterproof polyurethane composite coating and preparation process thereof
By preparing quercetin-grafted composite fillers and modified isophorone diisocyanate solution, combined with raw materials such as polybutylene adipate, a polyurethane composite coating is formed, which solves the problems of waterproofness, heat resistance and UV aging resistance of water-based polyurethane coatings and achieves long-term stability and durability of the coating.
Patent Information
- Application Number
- CN202511140158.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-14
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-08-14
AI Technical Summary
Existing water-based polyurethane coatings have poor water resistance when exposed to water, and insufficient heat aging and UV aging resistance, which causes the coating to easily degrade and shortens its service life.
By preparing quercetin-grafted composite fillers and modified isophorone diisocyanate solution, combined with raw materials such as polybutylene adipate, a polyurethane composite coating is formed. The chemical bonding of quercetin and the scattering and reflection of ultraviolet rays by nano-silica are utilized to enhance the hydrophobicity and anti-ultraviolet aging properties of the coating.
The water resistance, heat resistance and UV aging resistance of the polyurethane composite coating are improved, and the service life of the coating is extended.
Smart Images

Figure CN120795770A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of polyurethane coatings, in particular to a waterproof polyurethane composite coating and a preparation process thereof. BACKGROUND
[0002] Waterborne polyurethane (WPU) has been widely used as a surface coating of automotive electronic devices and vehicle body materials due to its excellent mechanical properties, abrasion resistance and corrosion resistance, which can not only form an additional protective and external stress bearing area on the surface of the substrate, but also repair material defects and improve surface roughness due to its excellent flexibility.
[0003] In the preparation process of waterborne polyurethane, in order to realize its dispersibility in water, hydrophilic groups such as carboxyl groups in dimethylol butyric acid need to be introduced, which form ionic structures by neutralization (such as reaction with triethylamine to form carboxylate), so that the polyurethane molecules can be stably dispersed in water, but after film formation, these hydrophilic groups do not completely disappear and remain in the coating, when the coating contacts moisture, the hydrophilic groups will form hydrogen bonds or polar attraction with water molecules, resulting in the adsorption of water molecules on the surface of the coating or even into the interior, thereby reducing the water resistance; in addition, the molecular chain of waterborne polyurethane is composed of soft segments and hard segments, wherein the soft segment accounts for a high proportion and has a low bond energy, which is easily oxidized to generate peroxide at high temperature, thereby causing molecular chain rupture, resulting in poor heat aging resistance; and ultraviolet light can directly damage the chemical bonds of the molecular chain of waterborne polyurethane, causing the coating to degrade, and the compatibility of directly adding an ultraviolet resistant agent in a waterborne system is poor, which is easy to migrate or volatilize with moisture, resulting in ineffective inhibition of molecular chain aging and degradation at high temperature, further aggravating the aging of the coating.
[0004] Therefore, it is necessary to provide a waterproof polyurethane composite coating with heat aging and ultraviolet aging resistance and a preparation process thereof to prolong its service life. SUMMARY
[0005] In view of the deficiencies in the prior art, the purpose of the present application is to provide a waterproof polyurethane composite coating and a preparation process thereof.
[0006] The present application provides a preparation process of a waterproof polyurethane composite coating, comprising the following steps: S1: preparing a quercetin grafted composite filler After the magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved, they are mixed with a nano-silica dispersion liquid, then a mixed alkali solution is added for reaction, and after hydrothermal crystallization, 3-aminopropyl triethoxysilane is used for amination modification, and finally a grafting reaction with quercetin is carried out to obtain a quercetin grafted composite filler; S2: preparing a modified isophorone diisocyanate solution After dissolving 3,5-di-tert-butyl-4-hydroxybenzoic acid, isophorone diisocyanate is added to react, to obtain a modified isophorone diisocyanate solution; S3: preparing a polyurethane composite coating S3.1: adding polybutylene glycol adipate, dimethylol butyric acid and dibutyltin dilaurate into the above modified isophorone diisocyanate solution, and heating and stirring to react at 65-70℃ for 3-4h to obtain a prepolymer; S3.2: adding 2-hydroxy-5-substituted long-chain fatty acyloxybenzoic acid methyl ester into the above prepolymer, and heating and stirring to react for 2-3h, then adding trimethylolpropane, and continuing to react for 2-3h to obtain a precursor solution; S3.3: adding 1,4-butanediol into the above precursor solution, and continuing to stir to react for 1-2h, then adding triethylamine and acetone when the temperature is cooled to 35℃, and stirring to mix, then adding the above quercetin grafted composite filler, and fully mixing to be uniform, then adding water to emulsify to obtain a polyurethane composite coating.
[0007] Further, S1 specifically comprises the following steps: S1.1: adding nanosilica into deionized water at 1g: (40-50)mL, and ultrasonic dispersing for 30-40min to obtain a nanosilica dispersion; S1.2: adding magnesium nitrate hexahydrate and aluminum nitrate nonahydrate into deionized water at (1.7-1.8)g:1g:(10-16)mL, fully stirring and dissolving, then adding the above nanosilica dispersion, stirring to mix, then adding a mixed alkali solution at 2-4mL / min to adjust pH to 9-10, and continuing to stir for 1-2h to obtain a precursor solution; S1.3: transferring the above precursor solution into a high-pressure reaction kettle, and crystallizing at 75-85℃ for 10-12h, then naturally cooling to room temperature, and performing centrifugal separation, washing to neutral, vacuum drying and grinding to obtain a composite filler; S1.4: adding 3-aminopropyltriethoxysilane into an ethanol solution with a volume fraction of 90% at 1g:(100-200)mL, and adding glacial acetic acid to adjust pH to 4-5, stirring to hydrolyze for 20-30min, then adding the above composite filler at 1g:(10-20)mL, and heating and stirring to react at 50-60℃ for 4-5h, then cooling, and performing centrifugal separation, washing and vacuum drying to obtain an aminated composite filler; S1.5: quercetin, p-toluenesulfonic acid and hydroquinone are added into anhydrous ethanol according to (0.8-1) g: (0.05-0.1) g: 0.01 g: (90-100) mL, heated and stirred to dissolve at 50-60℃, then 1 g: (20-30) mL of the above-mentioned aminated composite filler is added, and heated and stirred to reflux at 70-80℃ for 5-6 h under nitrogen protection, cooled, centrifuged, washed and vacuum dried to obtain a quercetin grafted composite filler.
[0008] Further, S2 specifically comprises the following steps: S2.1: 3,5-di-tert-butyl-4-hydroxybenzoic acid is added into anhydrous acetone according to 1 g: (10-20) mL, heated and stirred to dissolve at 50-60℃ to obtain a 3,5-di-tert-butyl-4-hydroxybenzoic acid solution; S2.2: when the above-mentioned 3,5-di-tert-butyl-4-hydroxybenzoic acid solution is cooled to 40℃, 2,6-di-tert-butyl-p-cresol and dibutyltin dilaurate are added, stirred and mixed, then isophorone diisocyanate is added at 3-5 mL / min, and heated to react at 60-65℃ for 2.5-3.5 h under nitrogen protection to obtain a modified isophorone diisocyanate solution.
[0009] Further, the mass ratio of nano-silicon dioxide to magnesium nitrate hexahydrate is 1: (8-10).
[0010] Further, the mixed alkali solution is prepared by dissolving sodium hydroxide and sodium carbonate in deionized water according to solid-liquid ratio (3.8-4) g: 1 g: (45-50) mL.
[0011] Further, the amount of dibutyltin dilaurate added is 0.3-0.4% of the mass of 3,5-di-tert-butyl-4-hydroxybenzoic acid.
[0012] Further, the amount of 2,6-di-tert-butyl-p-cresol and dibutyltin dilaurate added is equal.
[0013] Further, the molar ratio of isophorone diisocyanate to 3,5-di-tert-butyl-4-hydroxybenzoic acid is 2:1.
[0014] Further, the raw material composition of the polyurethane composite coating is 90-100 parts of polybutylene glycol adipate, 70-80 parts of modified isophorone diisocyanate solution, 10-12 parts of quercetin grafted composite filler, 9-11 parts of dimethylol butyric acid, 7-9 parts of 2-hydroxy-5-substituted long-chain fatty acyloxybenzoic acid methyl ester, 5-6 parts of trimethylolpropane, 3-5 parts of 1,4-butanediol, 0.06-0.1 parts of dibutyltin dilaurate, 1.4-1.8 parts of triethylamine, 20-30 parts of acetone and 50-60 parts of water.
[0015] A waterproof polyurethane composite coating prepared by the preparation process of any one of the above.
[0016] The present application has the following advantages: 1、In the present application, by mixing polybutylene adipate, dimethylol butyric acid and dibutyltin dilaurate with modified isophorone diisocyanate solution for pre-polymerization, then adding 2-hydroxy-5-substituted long-chain fatty acyl oxybenzoic acid methyl ester for reaction, long-chain fatty acyl oxy and methyl benzoate structure are introduced into the polyurethane molecular chain, and trimethylolpropane is added for crosslinking reaction to increase the crosslinking degree of the molecular chain, and finally 1,4-butanediol is added as a chain extender to react with the remaining -NCO, after neutralization with triethylamine, viscosity reduction with acetone and emulsification with water to form a polyurethane composite coating, the introduction of long-chain fatty acyl oxy will enrich on the surface of the coating, forming a hydrophobic barrier to reduce the penetration of water molecules in the coating, while also reducing the surface energy of the coating, thereby effectively improving the water resistance of the polyurethane composite coating, at the same time, the polar groups in 2-hydroxy-5-substituted long-chain fatty acyl oxybenzoic acid methyl ester can interact with the substrate to enhance the interfacial bonding strength, the long-chain structure can increase the flexibility and entanglement ability of the polyurethane molecular chain, and the aromatic ring in the methyl benzoate structure can enhance the intermolecular interaction, further improving the bonding stability between the coating and the substrate, so the adhesion of the polyurethane composite coating can be effectively improved.
[0017] 2、In the present application, after 3,5-di-tert-butyl-4-hydroxybenzoic acid is dissolved, isophorone diisocyanate is added under the catalysis of dibutyltin dilaurate to react, and 3,5-di-tert-butyl-4-hydroxybenzoic acid is introduced into the isophorone diisocyanate molecule to prepare modified isophorone diisocyanate, which is used together with polybutylene adipate to prepare a polyurethane composite coating, 3,5-di-tert-butyl-4-hydroxybenzoic acid can produce free radical reaction under high temperature to terminate the free radical chain oxidation reaction and inhibit the oxidative degradation of the coating, thereby improving its heat aging resistance, at the same time, the introduction of tert-butyl and benzene ring structure in 3,5-di-tert-butyl-4-hydroxybenzoic acid can further enhance the hydrophobicity of the molecular chain, thereby improving the water resistance of the coating.
[0018] 3. In the present invention, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved, mixed with a nano-silica dispersion, and a mixed alkali solution is added for co-precipitation, and then hydrothermal crystallization is performed through a high-pressure hydrothermal reaction to prepare a composite filler, which is then subjected to amino surface modification using 3-aminopropyltriethoxysilane, and then reacted with quercetin to graft quercetin onto the surface of the composite filler. After the quercetin-grafted composite filler is prepared, the quercetin can be uniformly dispersed in the coating matrix along with the composite filler carrier, and after the quercetin is grafted onto the surface of the composite filler through chemical bonding, the quercetin can be carried out through the carrier. The polyurethane body is "woven" in the cross-linked network, and migration requires the destruction of chemical bonds. Therefore, it can inhibit the migration of quercetin in the coating matrix, thereby effectively improving the long-term UV aging resistance of the coating. In addition, the nano-silica in the composite filler can scatter and reflect ultraviolet rays, and hydrotalcite can delay the propagation path of ultraviolet rays through physical blocking effect. The conjugated double bonds and phenolic hydroxyl groups in the quercetin molecule can absorb ultraviolet rays, avoid direct ultraviolet radiation to the polyurethane molecular chain, and reduce the photooxidative degradation of the molecular chain. Therefore, quercetin and composite fillers can also synergistically improve the UV aging resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a flow chart of the preparation process of the waterproof polyurethane composite coating used in an embodiment of the present invention. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0021] Example 1, a preparation process of a waterproof polyurethane composite coating, such as Figure 1 As shown, the following steps are included: S1: Preparation of quercetin-grafted composite fillers S1.1: Add 1g of nano-silica to 40mL of deionized water and ultrasonically disperse for 30 minutes to obtain a nano-silica dispersion. S1.2: Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water at a ratio of 1.7 g:1 g:10 mL, and after thorough stirring to dissolve, the above-mentioned nano-silica dispersion was added. After stirring and mixing, a mixed alkaline solution was added at a rate of 2 mL / min, the pH was adjusted to 9, and stirring was continued for 1 hour to obtain a precursor solution, wherein the mass ratio of nano-silica to magnesium nitrate hexahydrate was 1:8, and the mixed alkaline solution was prepared by dissolving sodium hydroxide and sodium carbonate in deionized water at a solid-liquid ratio of 3.8 g:1 g:45 mL; S1.3: The precursor solution is transferred into a high-pressure reactor, and crystallized at 75℃ for 10h. After natural cooling to room temperature, the product is separated by centrifugation, washed to neutral, vacuum dried and ground to obtain the composite filler; S1.4: 3-aminopropyltriethoxysilane is added into a 90% volume fraction ethanol solution at 1g:100mL, and glacial acetic acid is added to adjust the pH to 4. After stirring for 20min, the above-mentioned composite filler is added at 1g:10mL. The mixture is heated and stirred at 50℃ for 4h. After cooling, the product is separated by centrifugation, washed and vacuum dried to obtain the aminated composite filler; S1.5: Quercetin, p-toluenesulfonic acid and hydroquinone are added into anhydrous ethanol at 0.8g:0.05g:0.01g:90mL. After heating and stirring to dissolve at 50℃, the above-mentioned aminated composite filler is added at 1g:20mL. The mixture is heated and stirred to reflux at 70℃ for 5h under nitrogen protection. After cooling, the product is separated by centrifugation, washed and vacuum dried to obtain the quercetin grafted composite filler; S2: Preparation of modified isophorone diisocyanate solution S2.1: 3,5-di-tert-butyl-4-hydroxybenzoic acid is added into anhydrous acetone at 1g:10mL. The mixture is heated and stirred to dissolve at 50℃ to obtain a 3,5-di-tert-butyl-4-hydroxybenzoic acid solution; S2.2: When the temperature of the above-mentioned 3,5-di-tert-butyl-4-hydroxybenzoic acid solution is reduced to 40℃, 2,6-di-tert-butyl-p-cresol and dibutyltin dilaurate are added. After stirring and mixing, isophorone diisocyanate is added at 3mL / min. The mixture is heated and reacted at 60℃ for 2.5h under nitrogen protection to obtain a modified isophorone diisocyanate solution. The amount of dibutyltin dilaurate added is 0.3% of the mass of 3,5-di-tert-butyl-4-hydroxybenzoic acid. The amounts of 2,6-di-tert-butyl-p-cresol and dibutyltin dilaurate are equal. The molar ratio of isophorone diisocyanate to 3,5-di-tert-butyl-4-hydroxybenzoic acid is 2:1; S3: Preparation of polyurethane composite coating S3.1: Polybutylene glycol adipate, dimethylol butyric acid and dibutyltin dilaurate are added into the above-mentioned modified isophorone diisocyanate solution. The mixture is heated and stirred to react at 65℃ for 3h to obtain a prepolymer; S3.2: 2-hydroxy-5-substituted long-chain fatty acyloxybenzoic acid methyl ester is added into the above-mentioned prepolymer. The mixture is heated and stirred to react for 2h. Trimethylolpropane is then added, and the reaction is continued for 2h to obtain a precursor solution; S3.3: adding 1,4-butanediol into the above precursor solution, continuing to stir the reaction for 1 h, adding triethylamine and acetone after the temperature is lowered to 35℃, stirring the mixture, then adding the above quercetin grafted composite filler, fully mixing and uniformizing, then adding water to emulsify, to obtain a polyurethane composite coating, wherein the raw material composition of the polyurethane composite coating is 90 parts of polybutylene glycol adipate, 70 parts of modified isophorone diisocyanate solution, 10 parts of quercetin grafted composite filler, 9 parts of dimethylol butyric acid, 7 parts of 2-hydroxy-5-substituted long-chain fatty acyl oxyl benzoic acid methyl ester, 5 parts of trimethylolpropane, 3 parts of 1,4-butanediol, 0.06 parts of dibutyltin dilaurate, 1.4 parts of triethylamine, 20 parts of acetone and 50 parts of water.
[0022] Example 2, a preparation process of a waterproof polyurethane composite coating, as shown in Figure 1 , comprising the following steps: S1: preparing a quercetin grafted composite filler S1.1: adding nanosilica into deionized water at 1 g: 45 mL, ultrasonic dispersing for 35 min to obtain a nanosilica dispersion; S1.2: adding magnesium nitrate hexahydrate and aluminum nitrate nonahydrate into deionized water at 1.75 g: 1 g: 13 mL, fully stirring and dissolving, then adding the above nanosilica dispersion, stirring and mixing, then adding a mixed alkali solution at 3 mL / min, adjusting the pH to 9.5, and continuing to stir for 1.5 h to obtain a precursor solution, wherein the mass ratio of nanosilica to magnesium nitrate hexahydrate is 1:9, and the mixed alkali solution is prepared by dissolving sodium hydroxide and sodium carbonate in deionized water at a solid-liquid ratio of 3.9 g: 1 g: 47 mL; S1.3: transferring the above precursor solution into a high-pressure reaction kettle, crystallizing at 80℃ for 11 h, naturally cooling to room temperature, then centrifuging, washing to neutral, vacuum drying and grinding to obtain a composite filler; S1.4: adding 3-aminopropyltriethoxysilane into an ethanol solution with a volume fraction of 90% at 1 g: 150 mL, and adding glacial acetic acid to adjust the pH to 4.5, stirring and hydrolyzing for 25 min, then adding the above composite filler at 1 g: 15 mL, heating and stirring at 55℃ for 4.5 h, cooling, then centrifuging, washing and vacuum drying to obtain an aminated composite filler; S1.5: adding quercetin, p-toluenesulfonic acid and hydroquinone into anhydrous ethanol at 0.9 g: 0.08 g: 0.01 g: 95 mL, heating and stirring to dissolve at 55℃, then adding the above aminated composite filler at 1 g: 25 mL, and heating and stirring to reflux under nitrogen protection at 75℃ for 5.5 h, cooling, then centrifuging, washing and vacuum drying to obtain a quercetin grafted composite filler; S2: Preparation of modified isophorone diisocyanate solution S2.1: 3,5-di-tert-butyl-4-hydroxybenzoic acid was added to anhydrous acetone at 1 g: 15 mL, heated and stirred to dissolve at 55°C to obtain a 3,5-di-tert-butyl-4-hydroxybenzoic acid solution; S2.2: When the temperature of the above 3,5-di-tert-butyl-4-hydroxybenzoic acid solution was reduced to 40°C, 2,6-di-tert-butyl-p-cresol and dibutyltin dilaurate were added, stirred and mixed, then isophorone diisocyanate was added at 4 mL / min, and reacted under nitrogen protection at 63°C for 3h to obtain a modified isophorone diisocyanate solution, wherein the amount of dibutyltin dilaurate added was 0.35% of the mass of 3,5-di-tert-butyl-4-hydroxybenzoic acid, the amount of 2,6-di-tert-butyl-p-cresol and dibutyltin dilaurate was equal, and the molar ratio of isophorone diisocyanate to 3,5-di-tert-butyl-4-hydroxybenzoic acid was 2:1; S3: Preparation of polyurethane composite coating S3.1: Polybutylene glycol adipate, dimethylol butanoic acid and dibutyltin dilaurate were added to the above modified isophorone diisocyanate solution, heated and stirred to react at 68°C for 3.5h to obtain a prepolymer; S3.2: 2-hydroxy-5-substituted long-chain fatty acyloxybenzoic acid methyl ester was added to the above prepolymer, and the mixture was stirred and reacted for 2.5h, then trimethylolpropane was added and the reaction was continued for 2.5h to obtain a precursor solution; S3.3: 1,4-butanediol was added to the above precursor solution, and the mixture was stirred and reacted for 1.5h, then triethylamine and acetone were added when the temperature was reduced to 35°C, the mixture was stirred and mixed, then the above quercetin grafted composite filler was added, the mixture was fully mixed and uniform, then water was added for emulsification to obtain a polyurethane composite coating, wherein the raw material composition of the polyurethane composite coating was 95 parts of polybutylene glycol adipate, 75 parts of modified isophorone diisocyanate solution, 11 parts of quercetin grafted composite filler, 10 parts of dimethylol butanoic acid, 8 parts of 2-hydroxy-5-substituted long-chain fatty acyloxybenzoic acid methyl ester, 5.5 parts of trimethylolpropane, 4 parts of 1,4-butanediol, 0.08 parts of dibutyltin dilaurate, 1.6 parts of triethylamine, 25 parts of acetone and 55 parts of water.
[0023] Example 3, a preparation process of a waterproof polyurethane composite coating, as shown in Figure 1 , comprising the following steps: S1: Preparation of quercetin grafted composite filler S1.1: Nano-silicon dioxide was added to deionized water at 1 g: 50 mL, and ultrasonic dispersion was carried out for 40 min to obtain a nano-silicon dioxide dispersion; S1.2: magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are added into deionized water at a ratio of 1.8 g: 1 g: 16 mL, after being fully stirred and dissolved, the above-mentioned nano-silica dispersion solution is added, after being stirred and mixed, a mixed alkali solution is added at a rate of 4 mL / min, the pH is adjusted to 10, and stirring is continued for 2 h to obtain a precursor solution, wherein the mass ratio of nano-silica to magnesium nitrate hexahydrate is 1:10, the mixed alkali solution is prepared by dissolving sodium hydroxide and sodium carbonate in deionized water at a solid-liquid ratio of 4 g: 1 g: 50 mL; S1.3: the above-mentioned precursor solution is transferred to a high-pressure reaction kettle, and crystallization is carried out at 85°C for 12 h, after natural cooling to room temperature, centrifugal separation, washing to neutral, vacuum drying and grinding are carried out to obtain a composite filler; S1.4: 3-aminopropyl triethoxysilane is added into a 90% volume fraction ethanol solution at a ratio of 1 g: 200 mL, and glacial acetic acid is added to adjust the pH to 5, after stirring and hydrolysis for 30 min, the above-mentioned composite filler is added at a ratio of 1 g: 20 mL, and heating and stirring are carried out at 60°C for 5 h, after cooling, centrifugal separation, washing and vacuum drying are carried out to obtain an aminated composite filler; S1.5: quercetin, p-toluenesulfonic acid and hydroquinone are added into anhydrous ethanol at a ratio of 1 g: 0.1 g: 0.01 g: 100 mL, after being dissolved by heating and stirring at 60°C, the above-mentioned aminated composite filler is added at a ratio of 1 g: 30 mL, and heating and stirring are carried out under nitrogen protection at 80°C for 6 h of reflux reaction, after cooling, centrifugal separation, washing and vacuum drying are carried out to obtain a quercetin grafted composite filler; S2: preparation of modified isophorone diisocyanate solution S2.1: 3,5-di-tert-butyl-4-hydroxybenzoic acid is added into anhydrous acetone at a ratio of 1 g: 20 mL, and dissolved by heating and stirring at 60°C to obtain a 3,5-di-tert-butyl-4-hydroxybenzoic acid solution; S2.2: after the temperature of the above-mentioned 3,5-di-tert-butyl-4-hydroxybenzoic acid solution is reduced to 40°C, 2,6-di-tert-butyl-p-cresol and dibutyltin dilaurate are added, after stirring and mixing, isophorone diisocyanate is added at a rate of 5 mL / min, and heated at 65°C for 3.5 h under nitrogen protection to obtain a modified isophorone diisocyanate solution, wherein the amount of dibutyltin dilaurate added is 0.4% of the mass of 3,5-di-tert-butyl-4-hydroxybenzoic acid, the amounts of 2,6-di-tert-butyl-p-cresol and dibutyltin dilaurate are equal, and the molar ratio of isophorone diisocyanate to 3,5-di-tert-butyl-4-hydroxybenzoic acid is 2:1; S3: preparation of polyurethane composite coating S3.1: polybutylene glycol adipate, dimethylol butanoic acid and dibutyltin dilaurate are added into the above-mentioned modified isophorone diisocyanate solution, and heated and stirred at 70°C for 4 h to obtain a prepolymer; S3.2: 2-hydroxy-5-substituted long-chain aliphatic acyloxy methyl benzoate is added to the prepolymer, and the reaction is stirred for 3 h, and then trimethylolpropane is added, and the reaction is continued for 3 h to obtain a precursor solution; S3.3: 1,4-butanediol is added to the precursor solution, and the reaction is stirred for 2 h, and then triethylamine and acetone are added when the temperature is lowered to 35°C, and then the quercetin grafted composite filler is added after stirring and mixing, and then water is added to emulsify to obtain a polyurethane composite coating, wherein the raw material composition of the polyurethane composite coating is 100 parts of polybutylene glycol adipate, 80 parts of modified isophorone diisocyanate solution, 12 parts of quercetin grafted composite filler, 11 parts of dimethylol butyric acid, 9 parts of 2-hydroxy-5-substituted long-chain aliphatic acyloxy methyl benzoate, 6 parts of trimethylolpropane, 5 parts of 1,4-butanediol, 0.1 parts of dibutyltin dilaurate, 1.8 parts of triethylamine, 30 parts of acetone, and 60 parts of water.
[0024] Comparative Example 1, which is different from Example 1 in that the 2-hydroxy-5-substituted long-chain aliphatic acyloxy methyl benzoate in step S4 is replaced with an equal amount of ethylenediamine.
[0025] Comparative Example 2, which is different from Example 1 in that step S2 is removed, and the modified isophorone diisocyanate solution in step S3 is replaced with an equal amount of isophorone diisocyanate-acetone solution, wherein the amount of isophorone diisocyanate in the isophorone diisocyanate-acetone solution is equal to the amount of modified isophorone diisocyanate in the modified isophorone diisocyanate solution.
[0026] Comparative Example 3, which is different from Example 1 in that the quercetin grafted composite filler in step S3 is replaced with quercetin and aminoized composite filler, wherein the amount of quercetin added is equal to the amount of quercetin in the quercetin grafted composite filler in Example 1, and the amount of composite filler added is equal to the amount of composite filler in the quercetin grafted composite filler in Example 1.
[0027] Comparative Example 4, which is different from Example 1 in that the quercetin grafted composite filler in step S3 is replaced with an equal amount of aminoized composite filler.
[0028] Comparative Example 5, which is different from Example 1 in that the quercetin grafted composite filler in step S3 is replaced with an equal amount of quercetin.
[0029] Test Example: Test 1: After the polyurethane composite coating prepared by Examples 1-3 and Comparative Example 1 was formed into a coating, the water resistance was tested according to GB / T1733-1993, and the adhesion was tested according to GB / T9286-2021, and the results are shown in Table 1.
[0030] Table 1: Water resistance and adhesion test results of polyurethane composite coating
[0031] From the above Table 1, it can be seen that in Comparative Example 1, the 2-hydroxy-5-substituted long-chain fatty acyloxy benzoic acid methyl ester is replaced with an equal amount of ethylenediamine, and the adhesion grade of the coating formed by the prepared polyurethane composite coating is 1, which is lower than that of Example 1, and after 720h water resistance test, blistering and peeling occur, while the coating prepared in Example 1 does not blister and peel. Therefore, by mixing polybutylene adipate, dimethylol butyric acid and dibutyl tin dilaurate with modified isophorone diisocyanate solution for pre-polymerization, then adding 2-hydroxy-5-substituted long-chain fatty acyloxy benzoic acid methyl ester for reaction, introducing long-chain fatty acyloxy and benzoic acid methyl ester structure into the polyurethane molecular chain, adding trimethylolpropane for crosslinking reaction to increase the crosslinking degree of the molecular chain, and finally adding 1,4-butanediol as a chain extender to react with the remaining -NCO, after neutralization with triethylamine, viscosity reduction with acetone and emulsification with water to prepare a polyurethane composite coating, the water resistance and adhesion of the polyurethane composite coating can be effectively improved.
[0032] Test 2: After the polyurethane composite coating prepared by Examples 1-3 and Comparative Example 2 was formed into a coating, the heat aging resistance and water resistance were tested, and the results are shown in Table 2.
[0033] Table 2: Heat aging resistance and water resistance performance test results of polyurethane composite coating
[0034] From the above Table 2, it can be seen that in Comparative Example 2, after grafting modification of 3,5-di-tert-butyl-4-hydroxy benzoic acid with isophorone diisocyanate, the coating prepared cracks after 72h baking at 200℃, and blisters after 720h water resistance test. Therefore, by dissolving 3,5-di-tert-butyl-4-hydroxy benzoic acid, adding isophorone diisocyanate under the catalysis of dibutyl tin dilaurate, and introducing 3,5-di-tert-butyl-4-hydroxy benzoic acid into isophorone diisocyanate molecules to prepare modified isophorone diisocyanate, the heat aging resistance and water resistance of the polyurethane composite coating prepared from the modified isophorone diisocyanate and polybutylene adipate can be improved.
[0035] Test 3: The polyurethane composite coating prepared in Examples 1-3 and Comparative Examples 3-4 was coated and then subjected to ultraviolet aging test in an ultraviolet aging test box with ultraviolet wavelength of 330 nm, radiation intensity of 50 W / cm2, and temperature of 48℃ for 168 h, and the results are shown in Table 3. 2
[0036] Table 3: Results of ultraviolet aging resistance test of polyurethane composite coating
[0037] As shown in Table 3, when quercetin was directly added into the coating with the amino-functionalized composite filler in Comparative Example 3, the coating formed by the polyurethane composite coating appeared cracks after ultraviolet aging for 168 h, indicating that quercetin can be uniformly dispersed in the coating matrix with the composite filler carrier after being grafted on the surface of the composite filler, and quercetin can inhibit the migration of quercetin in the coating matrix after being chemically grafted on the surface of the composite filler, thereby effectively improving the long-term ultraviolet aging resistance of the coating. In addition, when only the single amino-functionalized composite filler was added in Comparative Example 4, the coating formed by the polyurethane composite coating appeared cracks after ultraviolet aging for 168 h, and when only the single quercetin was added in Comparative Example 5, the coating formed by the polyurethane composite coating appeared cracks and peeled off after ultraviolet aging for 168 h, indicating that quercetin and the composite filler can synergistically improve the ultraviolet aging resistance of the coating.
[0038] It should be understood that, for those skilled in the art, improvements or changes can be made according to the above description, and all such improvements and changes shall fall within the scope of the appended claims of the present application. The parts not described in detail in the specification belong to the prior art known to those skilled in the art.
Claims
1. A preparation process for a waterproof polyurethane composite coating, characterized in that: The steps include: S1: Preparation of quercetin-grafted composite fillers Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved, mixed with a nano-silica dispersion, and then a mixed alkali solution is added to react. After hydrothermal crystallization, the mixture is amino-modified with 3-aminopropyltriethoxysilane, and finally grafted with quercetin to obtain a quercetin-grafted composite filler. S2: Preparation of modified isophorone diisocyanate solution After dissolving 3,5-di-tert-butyl-4-hydroxybenzoic acid, isophorone diisocyanate is added to react to obtain a modified isophorone diisocyanate solution; S3: Preparation of polyurethane composite coating S3.1: Add polybutylene adipate, dimethylolbutyric acid, and dibutyltin dilaurate to the modified isophorone diisocyanate solution, heat and stir at 65-70°C for 3-4 hours to obtain a prepolymer; S3.2: Add 2-hydroxy-5-substituted long-chain fatty acyloxybenzoic acid methyl ester to the above prepolymer, stir and react for 2-3 hours, then add trimethylolpropane and continue to react for 2-3 hours to obtain a precursor solution; S3.3: Add 1,4-butanediol to the above precursor solution and continue stirring to react for 1-2 hours. When the temperature drops to 35°C, add triethylamine and acetone, stir and mix, then add the above quercetin grafted composite filler, mix thoroughly, and add water for emulsification to obtain a polyurethane composite coating.
2. The preparation process of a waterproof polyurethane composite coating according to claim 1, characterized in that: S1 specifically includes the following steps: S1.1: Add 1g of nano-silica to (40-50)mL of deionized water and ultrasonically disperse for 30-40 minutes to obtain a nano-silica dispersion. S1.2: Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water at a ratio of (1.7-1.8) g: 1 g: (10-16) mL, stir thoroughly to dissolve, add the above-mentioned nano-silica dispersion, stir to mix, add the mixed alkaline solution at 2-4 mL / min, adjust the pH to 9-10, and continue stirring for 1-2 h to obtain a precursor solution; S1.3: Transfer the precursor solution to an autoclave and crystallize at 75-85°C for 10-12 hours. Cool naturally to room temperature, centrifuge, wash to neutrality, vacuum dry, and grind to obtain a composite filler. S1.4: Add 3-aminopropyltriethoxysilane to a 90% ethanol solution at a ratio of 1 g to (100-200) mL. Adjust the pH to 4-5 with glacial acetic acid and stir for 20-30 min. Then, add the composite filler at a ratio of 1 g to (10-20) mL. Heat and stir at 50-60°C for 4-5 h. After cooling, centrifuge, wash, and vacuum dry to obtain an amino-containing composite filler. S1.5: Add quercetin, p-toluenesulfonic acid and hydroquinone to anhydrous ethanol at a ratio of (0.8-1) g: (0.05-0.1) g: 0.01 g: (90-100) mL, heat and stir at 50-60°C to dissolve, then add the above-mentioned amino composite filler at a ratio of 1 g: (20-30) mL, and heat and stir under reflux at 70-80°C under nitrogen protection for 5-6 hours. After cooling, centrifuge, wash and vacuum dry to obtain a quercetin grafted composite filler.
3. The preparation process of a waterproof polyurethane composite coating according to claim 2, characterized in that: S2 specifically includes the following steps: S2.1: Add 1 g of 3,5-di-tert-butyl-4-hydroxybenzoic acid to anhydrous acetone at a ratio of (10-20) mL. Heat and stir at 50-60°C to dissolve the mixture to obtain a 3,5-di-tert-butyl-4-hydroxybenzoic acid solution. S2.2: When the temperature of the above 3,5-di-tert-butyl-4-hydroxybenzoic acid solution is cooled to 40°C, add 2,6-di-tert-butyl-p-cresol and dibutyltin dilaurate, stir and mix, then add isophorone diisocyanate at 3-5 mL / min, and heat the reaction at 60-65°C under nitrogen protection for 2.5-3.5 hours to obtain a modified isophorone diisocyanate solution.
4. The preparation process of a waterproof polyurethane composite coating according to claim 2, characterized in that: The mass ratio of nano-silicon dioxide to magnesium nitrate hexahydrate is 1:(8-10).
5. The preparation process of a waterproof polyurethane composite coating according to claim 2, characterized in that: The mixed alkaline solution is prepared by dissolving sodium hydroxide and sodium carbonate in deionized water at a solid-liquid ratio of (3.8-4) g:1 g:(45-50) mL.
6. The preparation process of a waterproof polyurethane composite coating according to claim 3, characterized in that: The added amount of dibutyltin dilaurate is 0.3-0.4% of the mass of 3,5-di-tert-butyl-4-hydroxybenzoic acid.
7. The preparation process of a waterproof polyurethane composite coating according to claim 3, characterized in that: The added amounts of 2,6-di-tert-butyl-p-cresol and dibutyltin dilaurate are equal.
8. The preparation process of a waterproof polyurethane composite coating according to claim 3, characterized in that: The molar ratio of isophorone diisocyanate to 3,5-di-tert-butyl-4-hydroxybenzoic acid is 2:
1.
9. The preparation process of a waterproof polyurethane composite coating according to claim 1, characterized in that: The raw material composition of the polyurethane composite coating is as follows, by mass: 90-100 parts of polybutylene adipate, 70-80 parts of modified isophorone diisocyanate solution, 10-12 parts of quercetin grafted composite filler, 9-11 parts of dihydroxymethylbutyric acid, 7-9 parts of 2-hydroxy-5-substituted long-chain fatty acyloxybenzoic acid methyl ester, 5-6 parts of trimethylolpropane, 3-5 parts of 1,4-butanediol, 0.06-0.1 parts of dibutyltin dilaurate, 1.4-1.8 parts of triethylamine, 20-30 parts of acetone and 50-60 parts of water.
10. A waterproof polyurethane composite coating, characterized in that: The waterproof polyurethane composite coating is prepared by the preparation process of any one of claims 1 to 9.
Citation Information
Patent Citations
Temperature-resistant waterproof polyurethane coating and preparation method thereof
CN119912865A
Wear-resistant waterborne polyurethane finish paint and preparation method thereof
CN120349717A
Process for preparing solvent-free aqueous polyurethane dispersion
US20170107319A1